Mengembangkan Kecerdasan Intrapersonal AUD Usia 5-6 Tahun Melalui Kegiatan Menggambar Bertema Di RA Ash-Shidiq Garut - Shelly Pratiwi; Anisa Anisa (LP2M STAI Al-Musaddadiyah Garut, 2026)
Intrapersonal intelligence is an important intelligence to develop because individuals who have high intrapersonal intelligence are more able to achieve success in their lives. The development of intrapersonal intelligence in children aged 5-6 years at RA Ash-Shidiq develops children's self-awareness, increases children's independence, and increases children's self-confidence in learning in the Raudhatul Athfal environment. So learning activities are needed that can develop intrapersonal intelligence in children from an early age. This research aims to describe the application of themed drawing activities and their influence in improving children's intrapersonal intelligence. The method used is classroom action research (PTK) with the Kemmis MC and Taggart models. The research was carried out in two cycles and each cycle consisted of two meetings, which consisted of planning, action, observation and reflection procedures. Data collection techniques in this research are through observation, interviews and documentation. The research results show that the increase in children's intrapersonal intelligence increases with each cycle. This was marked by an increase in the percentage of children's success, which was initially 22%, increased in cycle I to 59.3%, and in cycle II increased to 85.2%. So it can be concluded that the application of themed drawing activities can develop early childhood intrapersonal intelligence in children aged 5-6 years at RA Ash-Shidiq Garut. Keywords: Early Childhood, Intrapersonal Intelligence, Themed Drawing